Financial oil derivatives : from options to oil warrants and synthetic oilfields - Trabia, Xavier (UK : Oxford Institute for Energy Studies, 1992)
The book discusses the financial oil derivatives such as oil warrants and American future options.
O.I.E.S Papers on the world petroleum market
Includes bibliographical references.
rua 13/02/15
Loans
Keywords: Financial economics; Futures and Options Market